DAILY ACTIVITY OF JUVENILE JAVAN GIBBON (Hylobates moloch AUDEBERT 1798) IN GUNUNG HALIMUN SALAK NATIONAL PARK - Ivanna Febrissa; Dones Rinaldi (ZOO INDONESIA, 2020)
Javan gibbon (Hylobates moloch) is one of endemic primates in Java Island, which listed as endangered and facing the high risk of extinction. Conservation efforts need to be taken immediately in regard to the decrease of this species population. One of aspects that support conservation effort is data on daily activity of this species. The aim of this study was to determine the daily activities of Javan gibbon juvenile at Citalahab Forest Gunung Halimun Salak National Park. We used focal sampling method to collect behavioral data and recording the activity of each individual Javan gibbon by continuous recording. Average time the daily activities of the three groups is 9 hours 56 minutes. Percentage of daily activity from the highest to the lowest is the resting (36.21%), feeding (33.33%), moving (23.05%), socializing (4.94%) and undetected (2.47%). Mostly social activities that do by javan gibbon is play with most frequently performed is wrestling. Javan gibbon in Cikaniki – Citalahab used 11 species as food resource. There are four types of trees used as sleeping tree over the research. The dominant tree strata for sleeping tree is strata A (over 30 m).